Odyseja Polskiej Armii Blekitnej - Trawinski, Witold H. (Witold Hilary), 1894-1976.; Suleja, Wlodzimierz (Wroclaw : Zaklad Narodowy im. Ossolinskich, 1989)
A chronicle of the Polish army contingent that fought with the French on the Western Front during WW I.
Includes bibliographical references and index.
Keywords: Trawinski, Witold H. -- 1894-1976.; France. -- Armee. -- Legion polonaise; World War, 1914-1918 -- Regimental histories -- France; World War, 1914-1918 -- Personal narratives, Polish; Polish Americans -- Biography; World War, 1914-1918 -- Poland; Poland -- Armed Forces -- History -- World War, 1914-1918.